Optimalisasi Metode Response Policy Zone (RPZ) Internet Sehat pada Jaringan FTTH Prabumulih - Dicopran Sisco; Tata Sutabri (International Forum of Researchers and Lecturers, 2024)
Abstract. One example of advanced information and communication technology is the internet. One can readily obtain the knowledge they require thanks to the internet. As a result, the internet is a crucial tool that needs to be used and understood to the fullest. The internet may be used for both beneficial and harmful purposes, which is why it is a double-edged sword with all of its risks. By filtering negative content using a list of 773 thousand negative content blocked on the trust + ™ Positive website by the Ministry of Communication and Information, the author hopes to create a positive internet network in the Prabumulih community and enable effective and efficient use of internet resources. The author can create a favorable online environment in Prabumulih City by utilizing the action research approach and the policy zone response method.